Decellularization techniques of human foreskin for tissue engineering application - Novotná, Olga; Varchulová Nováková, Zuzana; Gálfiová, Paulína; Lorencová, Mária; Klein, Martin; Žiaran, Stanislav; Kuniaková, Marcela (Physiological research, 2023)
The rapid development of tissue engineering (TE) and regenerative medicine brings an acute need for biocompatible and bioactive biological scaffolds to regenerate or restore damaged tissue. Great attention is focused on the decellularization of tissues or even whole organs, and the subsequent colonization of such decellularized extracellular matrices by recipient cells. The foreskin is an integral, normal part of the external genitalia that forms the anatomical covering of the glans penis and the urinary meatus of all human and non-human primates. It is mucocutaneous tissue that marks the boundary between mucosa and skin. In this work, we compared two innovative decellularization techniques for human foreskins obtained from donors. We compared the efficacy and feasibility of these protocols and the biosafety of prepared acellular dermal matrixes that can serve as a suitable scaffold for TE. The present study confirms the feasibility of foreskin decellularization based on enzymatic or detergent methods. Both techniques conserved the ultrastructure and composition of natural ECM while being DNA-free and non-toxic, making it an excellent scaffold for follow-up research and TE applications.
Keywords: Extracellular Matrix; tkáňové podpůrné struktury; mužské pohlaví; lidé; Male; Animals; Foreskin; předkožka; extracelulární matrix; Regenerative Medicine; zvířata; Tissue Engineering; regenerativní lékařství; Humans; Tissue Scaffolds; tkáňové inženýrství